2021
DOI: 10.1111/pace.14314
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes in hospitalized patients undergoing pacemaker insertion: Analysis from the national inpatient database (2016‐2017)

Abstract: Background Pacemaker implantation in the U.S. is rising due to an aging population. The aim of this analysis was to identify risk factors associated with increased mortality and complications in hospitalized patients requiring pacemaker implantation. Methods We performed a retrospective analysis using the National Inpatient Sample database, identifying hospitalized patients who underwent pacemaker implantation using International Classification of Disease, Tenth Revision, Clinical Modification codes. Independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…The present study showed that malnutrition impacts in-hospital mortality after CIED implantations. The analysis by Kichloo et al confirmed our observations, as it indicated that malnutrition is one of the mortality predictors in hospitalizations involving pacemaker implantation [35]. Our study showed that a higher NRS 2002 score is associated with higher mortality among CIED-implanted patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study showed that malnutrition impacts in-hospital mortality after CIED implantations. The analysis by Kichloo et al confirmed our observations, as it indicated that malnutrition is one of the mortality predictors in hospitalizations involving pacemaker implantation [35]. Our study showed that a higher NRS 2002 score is associated with higher mortality among CIED-implanted patients.…”
Section: Discussionsupporting
confidence: 87%
“…There is published evidence for the role of malnutrition in long-term mortality after selected electrotherapy procedures, i.e., pacemakers, implantable cardioverter-defibrillator (ICD), or cardiac resynchronization therapy (CRT) implantations [ 32 , 33 , 34 ]. There is only one published study that showed a higher in-hospital mortality of malnourished patients undergoing pacemaker implantations [ 35 ]. There are no available publications that focus on in-hospital mortality after other types of CIED implantations.…”
Section: Introductionmentioning
confidence: 99%
“… 1 - 3 Estudos embasados em análise de dados de sistemas administrativos, entretanto, têm demonstrado aumento progressivo das taxas de complicações pós-operatórias e de readmissões hospitalares, que têm sido explicados, principalmente, pela fragilidade e pelas comorbidades desta população. 4 - 8 …”
Section: Introductionunclassified
“… 1 - 3 However, studies based on data analysis from administrative systems have demonstrated a progressive increase in the rates of postoperative complications and hospital readmissions, which have been mainly explained by the frailty and comorbidities of this population. 4 - 8 …”
Section: Introductionmentioning
confidence: 99%